USM-NUT COLLABORATION LED TO FORMATION OF GIGAKU TECHNO PARK - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
GEORGE TOWN, PENANG, 2 March 2016 – The collaboration and cooperation established between Universiti Sains Malaysia (USM) and Nagaoka University of Technology (NUT) Japan which had existed since 2005 is now strengthened further with the establishment of the USMNUT Gigaku Techno Park (USMNUT GTP) office at USM.